Mapping of neuropeptide Y expression in Octopus brains. (8th May 2020) - Winters, Gabrielle C.; Polese, Gianluca; Di Cosmo, Anna; Moroz, Leonid L.
Abstract: Neuropeptide Y (NPY) is an evolutionarily conserved neurosecretory molecule implicated in a diverse complement of functions across taxa and in regulating feeding behavior and reproductive maturation in Octopus . However, little is known about the precise molecular circuitry of NPY‐mediated behaviors and physiological processes, which likely involve a complex interaction of multiple signal molecules in specific brain regions. Here, we examined the expression of NPY throughout the Octopus central nervous system. The sequence analysis of Octopus NPY precursor confirmed the presence of both, signal peptide and putative active peptides, which are highly conserved across bilaterians. In situ hybridization revealed distinct expression of NPY in specialized compartments, including potential "integration centers, " where visual, tactile, and other behavioral circuitries converge. These centers integrating separate circuits may maintain and modulate learning and memory or other behaviors not yet attributed to NPY‐dependent modulation in Octopus . Extrasomatic localization of NPY mRNA in the neurites of specific neuron populations in the brain suggests a potential demand for immediate translation at synapses and a crucial temporal role for NPY in these cell populations. We also documented the presence of NPY mRNA in a small cell population in the olfactory lobe, which is a component of the Octopus feeding and reproductive control centers. However, the molecular mapping of NPY expression only partially overlapped with that produced by immunohistochemistry in previous studies. Our study provides a precise molecular map of NPY mRNA expression that can be used to design and test future hypotheses about molecular signaling in various Octopus behaviors. Abstract : Neuropeptide Y (NPY), an evolutionarily conserved neurosecretory molecule, is expressed in specialized regions of the Octopus brain controlling feeding, reproduction, and visual and tactile memory circuits. Extrasomatic mRNAs were found in neurites, suggesting synaptic synthesis of NPY.